Mysticism as the Locus of Inter-Faith Dialogue - Jayaceelan, R.J.E. (University of jaffna, 2018)
The document of the second Vatican Council on the church Lumen Gentium opined on the church as a sacrament of union with God and unity of all mankind. Again the document on non Christian religions Nostra Aetate opened its heart to all religions especially to Hinduism and Buddhism. “This document”, said Claude Nelson “may prove to be even more important than… Buddhism in its multiple forms acknowledges the radical insufficiency of this shifting world.” NA5. Cardinal Hentry Lubac wrote his ‘The drama of atheistic Humanism’ pointing to the rise of an atheistic humanism as a weltanschauung, the need for a Christian humanism to counteract it. His work on Buddhism later, in response to this call of Thomas Merton a Trappist monk of Gethsemani, Kentucky, USA was moving toward ZEN. He journeyed from English literature to justice, non violence, after Second World War to Gandhi and to Chuang Tzu who spoke with said, ‘Zen TEACHES NOTHING, it merely enables us to wake up and become aware. It does not teach, it points. Bodhiddharma, a Tamil Buddhist from Kanchi, was the first missionary to china and stated that, ‘Zen’ is a special transmission outside scriptures, not founded upon words and letters. By pointing to one’s mind, long before Merton, Enomiya Lasalle and Herinrich Dumoullin, two Jesuits studied and practiced Zen before the Second World War. Dumuollin said, “whereas the Indians were inhabited by their agonizing struggle for salvation, the Chinese who desired nothing so much as to penetrate the secrets of nature abandoned themselves completely to the Tao, the Buddhist Naturalism. A.M.A Samy of Dindugal is the present guru of Christian Zen. Joseph Vaz and the Oratorians introduced us to a type of new Christian Zen humanism. European humanism and the civil war made us lose our transcendence and mysticism as Cardinal Malcom Ranjith asserts. He urges us to get back to our Catholic cultural roots and ETHOS. Can Christian Zen be of any help?
Keywords: Mysticism; Religions; Zen; Humanism; Awareness